2021
DOI: 10.1155/2021/5812499
|View full text |Cite|
|
Sign up to set email alerts
|

Influential Usage of Big Data and Artificial Intelligence in Healthcare

Abstract: Artificial intelligence (AI) is making computer systems capable of executing human brain tasks in many fields in all aspects of daily life. The enhancement in information and communications technology (ICT) has indisputably improved the quality of people’s lives around the globe. Especially, ICT has led to a very needy and tremendous improvement in the health sector which is commonly known as electronic health (eHealth) and medical health (mHealth). Deep machine learning and AI approaches are commonly presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 75 publications
0
22
0
3
Order By: Relevance
“…Third, few studies reported the cost and infrastructure of telecardiology, which represents an important issue in rural practice. Lastly, while newer technologies, such as artificial intelligence (AI) that is implied to improve medical practice [ 39 ], may be already introduced to rural practice, we could not find such a paper on the telecardiology combined with AI in rural practice. This is a limitation in the review based on the previously published literature.…”
Section: Discussionmentioning
confidence: 99%
“…Third, few studies reported the cost and infrastructure of telecardiology, which represents an important issue in rural practice. Lastly, while newer technologies, such as artificial intelligence (AI) that is implied to improve medical practice [ 39 ], may be already introduced to rural practice, we could not find such a paper on the telecardiology combined with AI in rural practice. This is a limitation in the review based on the previously published literature.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al 27 conducted a literature review on AI and big data applications in health care. The authors collected articles on different machine-learning algorithms to process big data regarding patient care.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Big data and AI have long since reached medicine ( Yang et al, 2021 ). This is no more than a truism.…”
Section: E-health In Preventive Health Care In General and In Pediatr...mentioning
confidence: 99%